Large scale miners - Communities partnerships: A plausible option for communities survival beyond mine closure - Zvarivadza, T. (Elsevier, 2022)
A sound relationship between Large Scale Mining/Miners (LSMs) and communities is key to a successful and mutually beneficial mining venture. This relationship has to be carefully managed to ensure a conducive operating environment. Merely sticking to the dictates of a government issued mining licence by LSMs and not facing reality on the ground may spark stiff resistance from the communities on which the mining company has to operate. Two competing priorities have to be balanced - the LSM, having a mining licence, argue that they have a legal right from the government to mine while the community, which have stayed on the mining area for generations, claim the area as their birth right and believe they inherently have the mining right. A well-coordinated consultative approach and cooperation with communities is vitally important in breaking this impasse. Community empowerment is one of the central themes discussed in the paper. The mining companies need to leave a lasting positive legacy for the communities so that they can sustain life well beyond mine closure. The mineral resource capital needs to be converted to other capitals on which the community can thrive well beyond mine closure. The paper discusses different strategies which can be adopted to ensure productive partnerships between LSMs and the communities to realise the lasting positive legacy. The strategies include: investment in education, which may lead to employment in other sectors of the economy, establishment of survival community projects, investment in adequately managed community trusts, designation of areas amenable to Artisanal and Small Scale Mining (ASM), attainment of social licence to operate, procurement of labour from the communities wherever possible and strategic accommodation planning to avert ghost towns among others. Four compelling case studies are used to give impetus to the arguments expressed in the paper. These include the partnerships of the following LSMs with communities in their mining areas: Royal Bafokeng Holdings and the Roya Bafokeng Nation in South Africa, Zimbabwe Platinum Mines (Zimplats) and Mhondoro Ngezi, Chegutu and Zvimba communities in Zimbabwe, Anglo Gold Mining Company and Sadiola in Mali as well as Ghana Consolidated Diamonds and Akwatia in Ghana.